Maternal and fetal outcomes in pregnancy induced hypertensive patients and normotensive patients - Dev, Kapil; Sood, Rajeev; Sharma, Anoop (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorder of pregnancy complicates 5 to 8% of pregnancies and is a major cause of maternal and perinatal morbidity and mortality. Hypertensive disorders of pregnancy account for nearly 18% of all maternal deaths worldwide, with an estimated 62000-77000 deaths per year. Methods: This one-year prospective case control study total 200 pregnant women attending antenatal care and admitted in Eclampsia ward fulfilling the inclusion criteria were studied. Fetal and maternal outcomes data recorded and documented. Statistical analysis of data was done by student’s t-test and p-value. Results: In PIH 68% women had normal vaginal delivery (p=0.004) 10% women had instrumental delivery. In PIH group 22% women had emergency caesarian section and in normotensive group 10% women had emergency caesarian section. In PIH group 58% delivered at term and 42% had preterm delivery. In normotensive 95% delivered at term and 5% had preterm delivery (p <0.001). PIH group 29% women developed IUGR whereas in normotensive group all women had normal growth velocity (p <0.001). In PIH group 69% mothers had newborn with birth weight <2.5 kg and 31% women had newborn with birth weight >2.5 kg (p=0.0009). While In normotensive group only 9% women had newborn with birth weight <2.5 kg. In PIH group, 24% newborn babies needed NICU admission and in normotensive group only 5% newborn needed NICU admission (p=0.001). In PIH group 76% women had normal maternal outcome (p <0.001). 11% had associated abruption (p=0.0019). In the rest 13% patient develop PRES. Conclusions: We concluded that there is a significant rise of complication in mothers having PIH and also there is an increased risk of delivering low birth weight and preterm babies. The early use of antihypertensive drugs, optimum timing of delivery and strict fluid balance, anticonvulsants in cases of eclampsia will help to achieve successful outcome.